2019
DOI: 10.2298/abs180918055v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ibogaine per os application on redox homeostasis in rat liver and erythrocytes

Abstract: Ibogaine, administered as a single oral dose (1-25 mg/kg body weight), has been used as an addiction-interrupting agent. Its effects persist for up to 72 h. Ex vivo results showed that ibogaine induced cellular energy consumption and restitution, followed by increased reactive oxygen species production and antioxidant activity. Therefore, the aim of this work was to explore the effect of a single oral dose of ibogaine (1 or 20 mg/kg body weight) on antioxidative defenses in rat liver and erythrocytes. Six and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although ibogaine can act as a pro-antioxidant, promoting increased antioxidant activity in a dose-and time-dependent manner in different in vitro and ex vivo model systems, including yeast [7] and human erythrocytes [8], our recent in vivo findings [6] showed that ibogaine treatment influenced hepatic redox homeostasis, but not to a sufficient extent to remodel antioxidant enzyme activities at 6 and 24 h post ibogaine application. However, in vitro and ex vivo experiments were performed with much higher doses than used in vivo and per os application, where its pro-antioxidant ability in the liver was not as convincing [6]. Results showed that in vivo intragastric application in rats and mice led to much lower ibogaine and noribogaine concentrations in blood plasma [6,12] when compared to doses used in vitro.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Although ibogaine can act as a pro-antioxidant, promoting increased antioxidant activity in a dose-and time-dependent manner in different in vitro and ex vivo model systems, including yeast [7] and human erythrocytes [8], our recent in vivo findings [6] showed that ibogaine treatment influenced hepatic redox homeostasis, but not to a sufficient extent to remodel antioxidant enzyme activities at 6 and 24 h post ibogaine application. However, in vitro and ex vivo experiments were performed with much higher doses than used in vivo and per os application, where its pro-antioxidant ability in the liver was not as convincing [6]. Results showed that in vivo intragastric application in rats and mice led to much lower ibogaine and noribogaine concentrations in blood plasma [6,12] when compared to doses used in vitro.…”
Section: Discussionmentioning
confidence: 75%
“…However, in vitro and ex vivo experiments were performed with much higher doses than used in vivo and per os application, where its pro-antioxidant ability in the liver was not as convincing [6]. Results showed that in vivo intragastric application in rats and mice led to much lower ibogaine and noribogaine concentrations in blood plasma [6,12] when compared to doses used in vitro. Therefore, the pro-antioxidant role of ibogaine was questioned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations